2003
DOI: 10.1081/lft-120018537
|View full text |Cite
|
Sign up to set email alerts
|

Solid Petroleum Asphaltenes Seem Surrounded by Alkyl Layers

Abstract: In this review, a comprehensive analysis of recent results obtained in our laboratory and published in the literature is presented, which points toward the existence of alkyl layers surrounding precipitated asphaltene solids. A micellar model for asphaltenes has been proposed, which explains many of the experimental determinations carried out to date with these compounds. The model considers the existence of alkyl moieties surrounding the inner aromatic cores. Faster dissolution kinetics of asphaltenes modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 31 publications
5
15
0
Order By: Relevance
“…The authors observed similar trends for the parent whole crude oil, thereby suggesting that interactions between aliphatic moieties could be central in petroleum and asphaltene aggregation. These results are consistent with the idea that London forces between alkyl side chains drive the self-assembly of asphaltene nanoaggregates to produce more massive clusters, widely reported by Rogel, Carbognani, and Stachowiak et al …”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…The authors observed similar trends for the parent whole crude oil, thereby suggesting that interactions between aliphatic moieties could be central in petroleum and asphaltene aggregation. These results are consistent with the idea that London forces between alkyl side chains drive the self-assembly of asphaltene nanoaggregates to produce more massive clusters, widely reported by Rogel, Carbognani, and Stachowiak et al …”
Section: Introductionsupporting
confidence: 92%
“…The authors observed similar trends for the parent whole crude oil, thereby suggesting that interactions between aliphatic moieties could be central in petroleum and asphaltene aggregation. These results are consistent with the idea that London forces between alkyl side chains drive the self-assembly of asphaltene nanoaggregates to produce more massive clusters, widely reported by Rogel, 64 Carbognani, 65 and Stachowiak et al 66 It is critical to point out that there is not a clear correlation between asphaltene aggregation in industrial applications (e.g., fouling in production facilities) and GPC elution trends. For example, Muller et al 67,68 fractionated geologically diverse crude oils by GPC and used off-line FT-ICR MS for molecular characterization.…”
Section: ■ Introductionsupporting
confidence: 88%
“…GPC FT-ICR MS results are consistent with several works that suggest that London forces between aliphatic moieties might be central in asphaltene aggregation. For instance, the self-aggregation nature of model asphaltene compounds, with varying content of aliphatic chains and heteroatomic functionalities, was tested by molecular dynamics simulations . The authors observed a direct correlation between increased dissociation energy and higher contents of aliphatic chains and heteroatoms.…”
Section: A Comprehensive Analytical Approach To Understand Ultracompl...supporting
confidence: 85%
“…Carbognani and Rogel realized a study of dissolution kinetics for wax in toluene at 25 °C using pure asphaltenes and complex mixtures formed for these fractions, to observe the interaction among each other. The authors found that the unstable asphaltenes have proved to be highly aromatic and devoid of alkyl appendages.…”
Section: Introductionmentioning
confidence: 99%